Assessment of Housing Challenges in Higher Institutions in Nigeria: A Case Study of Federal Polytechnic, Ilaro (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Access to adequate housing remains a persistent challenge for staff and students of higher education institutions in Nigeria. Growing student enrolment, insufficient on-campus residential facilities, and escalating private rents have widened the gap between housing demand and supply. This study examined housing challenges at Federal Polytechnic Ilaro (FPI), Ogun State, Nigeria. Data were collected through structured questionnaires administered to 83 staff and students, a physical condition survey of 100 housing units, and GPS mapping of residential locations and the road network. Geospatial analysis was performed in ArcGIS 10.6.1, and quantitative analysis combined frequency distributions, the Weighted Preference Index (WPI), the Relative Preference Ratio (RPR), binomial tests, two-proportion z-tests, goodness-of-fit chi-square tests, a Housing Condition Index (HCI), and a rent-to-income (RTI) ratio analysis. The results indicate that 44.58% of respondents reside in privately rented accommodation and 55.42% commute between 15 and 30 minutes daily. 52% of the sampled house unity have access, a proportion not significantly above 50% (p = 0.764). These suggest there is effective random access to electricity. Security fence were present in 85% of units (p < 0.001), significantlsy exceeding both water (z = 3.959, p < 0.001) and electricity access (z = 5.023, p < 0.001). The HCI found that 26% of units fall in poor or severely deprived categories. The modal rent band of ₦150,000–₦350,000 corresponds to a rent-to-income ratio of 29.8% of the annual minimum wage, approaching the 30% affordability threshold. Salary-deductible housing loans (WPI = 0.811) and a dedicated transport service (WPI = 0.803, RPR = 4.78) were the most preferred interventions. The study recommends salary-deductible loan schemes, a dedicated shuttle service, public-private partnerships for hostel construction, and engagement with local authorities on rental price guidelines.